2012
DOI: 10.1016/j.pedneo.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The Macronutrients in Human Milk Change after Storage in Various Containers

Abstract: Human milk, when subjected to storage, freezing, and thawing processes, demonstrated a significant decrease in fat content (up to 9% reduction) in various containers. It is better for infants to receive milk directly from the mother via breastfeeding. More studies are warranted to evaluate the effects of milk storage on infant growth and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 28 publications
2
50
0
1
Order By: Relevance
“…Fat is known to be the most variable macronutrient in human milk. It has been reported that fat content varies depending on maternal diet [14], morning/night [16], hind-or fore-milk [19] and storage conditions [6]. In our study median fat concentrations in HM were 3.5 g/100.…”
Section: Discussionsupporting
confidence: 43%
“…Fat is known to be the most variable macronutrient in human milk. It has been reported that fat content varies depending on maternal diet [14], morning/night [16], hind-or fore-milk [19] and storage conditions [6]. In our study median fat concentrations in HM were 3.5 g/100.…”
Section: Discussionsupporting
confidence: 43%
“…HM expression and expressed‐HM feeding are of public health importance because, depending on the location and duration of storage, expressed HM loses important nutritional (Chang et al . ; Romeu‐Nadal et al . ) and functional (Hanna et al .…”
Section: Introductionmentioning
confidence: 99%
“…HM expression and expressed-HM feeding are of public health importance because, depending on the location and duration of storage, expressed HM loses important nutritional (Chang et al 2012;Romeu-Nadal et al 2008) and functional (Hanna et al 2004;Silvestre et al 2006) components. Short-term storage of HM reduces the concentration of vitamin C (Garza et al 1982), with increased duration of storage in the freezer causing a more marked decrease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, carbonyl groups (5.7 µm) and carbon hydrogen groups (3.5 µm) were chosen for fat determination, amide groups (6.5 µm) for protein determination and hydroxyl groups (9.6 µm) for lactose determination (Sjaunja, ; Biggs et al , ; Biggs and Mckenna, ). The results of the analysis are available within approximately 1 min after a milk sample is injected (Chang et al, ). These instruments were calibrated with known protein, fat and lactose concentration milk measured by chemical methods.…”
Section: Introductionmentioning
confidence: 99%